(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
Many empirical studies state that retail gasoline and diesel prices react more quickly when the crude oil price rises rather than decreases. In the paper, we confirm these asymmetric reactions of retail fuel prices in selected cities in the United States of America. We use the adjustment cost function in the linear-exponential form to derive nonlinear retail gasoline and diesel reaction functions. The correspondent model is estimated with the system’s generalised method of moments. The model allows us to compute average one-gallon gasoline and diesel price biases from the increase in oil by one dollar per barrel caused by the given asymmetric reactions. The average biases differ from city to city; their values are between 0.02 cents in Los Angeles and 0.44 cents in Cleveland.